Determinants of Credit Distribution Levels at Book 4 Banks in Indonesia from 2015 to 2024 - Putri, Anastasia Yolanda; Hasyim, Sirojuzilam; Syafii, M. (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyse the factors influencing the credit distribution rate at Book 4 banks in Indonesia for the period 2015–2024. The variables studied include interest rates, exchange rates, economic growth, and money supply as independent variables. The credit distribution rate is used as the dependent variable. The research data uses panel data consisting of cross-sectional data from banks included in Book 4 banks and time series data for the 2015–2024 period. This study uses analysis with the panel data regression analysis method through an approach processed using the E-Views data processing application. The results show that, partially, interest rates and exchange rates have a negative and significant effect on the level of credit distribution in Book 4 banks in Indonesia, while the variables of economic growth and money supply have a positive and significant effect on the level of credit distribution in Book 4 banks in Indonesia. Simultaneously, interest rates, exchange rates, economic growth, and money supply have a positive and significant effect on the level of credit distribution in book 4 banks in Indonesia with an effect of 94.65%.